The girl who dared ebook - Shamsi, Shirin (2019)
Readers will be inspired by this immigration story about a young refugee whose family tries to emigrate to Pakistan when India is divided into two separate nations. This short, 32-page hi-lo book features full-color illustrations to capture the attention of kids who enjoy realistic fiction stories about characters who must overcome difficult circumstances in order to survive.